Reducing Loneliness Among Aging Adults: The Roles of Personal Voice Assistants and Anthropomorphic Interactions - Jones, Valerie K.; Hanus, Michael; Yan, Changmin; Shade, Marcia Y.; Blaskewicz Boron, Julie; Maschieri Bicudo, Rafael (Frontiers in Public Health, 2021)
The perception of feeling lonely is an influential factor in determining quality of life among aging adults. As the US Census Bureau projects that the number of Americans ages 65 and older will double by 2060, reducing loneliness is imperative. Personal voice assistants (PVAs) such as Amazon’s Echo offer the ease-of-use of voice control with a friendly, helpful artificial intelligence. This study aimed to understand the influence of a PVA on loneliness reduction among adults of advanced ages, i.e., 75+, and explore anthropomorphism as a potential underlying mechanism. Participants (N=16) ages 75 or older used an Amazon Echo PVA for eight weeks in an independent living facility in the Midwest. Surveys were used to collect information about perceived loneliness, and PVA interaction data was recorded and analyzed. Participants consistently exceeded the required daily interactions. As hypothesized, after the first four weeks of the intervention, aging adults reported significantly lower loneliness (baseline mean=2.22, SD=0.42; week 4 mean=1.99, SD=0.45, Z=-2.45, p=0.01). Four dominant anthropomorphic themes emerged after thematic analysis of the entire eight weeks’ PVA interaction data (Cohen’s Kappa = 0.92): 1) greetings (user-initiated, friendly phrases); 2) comments/questions (user-initiated, second-person pronoun), 3) polite interactions (user-initiated, direct-name friendly requests), 4) reaction (user response to Alexa). Relational greetings predicted loneliness reductions in the first four weeks and baseline loneliness predicted relational greetings with the PVA during the entire eight weeks, suggesting that anthropomorphization of PVAs may play a role in mitigating loneliness in aging adults.